2017
DOI: 10.1111/1745-9133.12295
|View full text |Cite
|
Sign up to set email alerts
|

Police Consent Decrees and Section 1983 Civil Rights Litigation

Abstract: Research SummarySection 14141 of the Violent Crime Control and Law Enforcement Act of 1994 granted the U.S. Department of Justice (DOJ) the authority to investigate, intervene into, and force reforms within any police department deemed to exhibit a pattern or practice of police misconduct. The DOJ's primary enforcement mechanism is to sue the offending jurisdiction. Such lawsuits are typically settled with “consent decrees” or court‐ordered legal agreements to implement specified reforms. We assembled a panel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…This information apprises social work practice by demonstrating the continuing need to construct a bridge between the two groups. Thus far, cities in agreement with the DOJ saw more than 20% reduction in filed civil rights lawsuits that involved police use of excessive force (Powell et al, 2017). Although there was not an immediate policy change after cities entered an agreement, cities are continuously working to improve their behavior and results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This information apprises social work practice by demonstrating the continuing need to construct a bridge between the two groups. Thus far, cities in agreement with the DOJ saw more than 20% reduction in filed civil rights lawsuits that involved police use of excessive force (Powell et al, 2017). Although there was not an immediate policy change after cities entered an agreement, cities are continuously working to improve their behavior and results.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to 2008, six cities entered a consent decree agreement (Upper Marlboro, MD; Detroit, MI; Los Angeles, CA; Newark, NJ; Steubenville, OH; and Pittsburgh, PA) and three were found to engage in excessive force practices (Los Angeles, Pittsburgh, and Steubenville) (US DOJ, 2017). Studies from these cities have reported more effective policing as a result of the consent decree; although limitations existed (Davis, Henderson, Mandelstam, Ortiz, & Miller, 2002;Powell, Meitl, & Worrall, 2017;Stone, Foglesong, & Cole, 2009).…”
mentioning
confidence: 99%
“…Most recently, Powell, Meitl, and Worrall (2017) conducted an empirical evaluation of civil litigation filed against agencies before and after they were subjected to CDs. Their hypothesis was that if the DOJ intervention was successful, then the number of Section 1983 lawsuits would decrease.…”
Section: Issues Of Evaluation and Sustainabilitymentioning
confidence: 99%
“…However, as Harmon (2017) notes in her responding essay, ''In fact, section 1983 suits are a poor proxy for constitutional violations (much less for misconduct more generally) because the incidence of civil suits rises and falls for reasons that are uncorrelated with police conduct'' (Draft, p. 2). In her thoughtful and wellargued essay, she explains the problems with measuring the success of CDs and commends Powell et al (2017) for their efforts and attempts to operationalize success. The conclusion reached by Powell et al is that CDs are likely associated with moderate reductions in filings of federal civil-rights lawsuits against officers or agencies (see Scott, 2017).…”
Section: Issues Of Evaluation and Sustainabilitymentioning
confidence: 99%
“…Several large metropolitan police departments have been found to participate in activities with inequitable impact on minority communities including racial profiling (Hughey, ; Vogelsang‐Coombs, ); or in extreme cases, torture (Baer, ). Consent decrees' have been implemented (Powell, Meitl, & Worrall, ) to reconcile these injustices. Criminologists are concerned with de‐policing, decreases in proactive policing within jurisdictions, yet the research is still largely inconsistent with some research indicating no such effect post‐Ferguson type events (Chanin & Sheats, ), while other research indicating an association that was largely driven by jurisdictions with larger shares of African‐American residents (Shjarback, Pyrooz, Wolfe, & Decker, ).…”
Section: Introductionmentioning
confidence: 99%